2022
DOI: 10.1007/s00167-022-07016-0
|View full text |Cite
|
Sign up to set email alerts
|

Femoral anteversion measured by the surgical transepicondylar axis is a reliable parameter for evaluating femoral rotational deformities in patients with patellar dislocation

Abstract: Purpose To verify whether femoral anteversion measured by the surgical transepicondylar axis (S-FA) is a reliable parameter for evaluating femoral rotational deformities and to provide an indication for derotational distal femoral osteotomy (DDFO) in patients with patellar dislocation. Methods Ninety patients with recurrent patellar dislocation and 90 healthy individuals were enrolled. The S-FA, the femoral anteversion measured by posterior condylar reference line (P-FA), the length of posterior femoral condyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…Recent studies by Zhao et al found that the main contributors to increased femoral anteversion in patients with patellar dislocation were the middle and distal femur [6], and other authors also discovered that the leading contributors to increased femoral anteversion were the middle and distal femur [7,8]. Chang and Li et al found that patients with severe valgus knees had greater femoral anteversion and dysplasia of the posterolateral condyle was also a key cause of femoral anteversion [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Zhao et al found that the main contributors to increased femoral anteversion in patients with patellar dislocation were the middle and distal femur [6], and other authors also discovered that the leading contributors to increased femoral anteversion were the middle and distal femur [7,8]. Chang and Li et al found that patients with severe valgus knees had greater femoral anteversion and dysplasia of the posterolateral condyle was also a key cause of femoral anteversion [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, a systematic review highlighted the importance of an accurate radiological evaluation to perform an individualized surgical strategy [ 8 ]. Using the posterior condylar reference line (P-tAV) to measure femoral anteversion cannot allow an accurate evaluation of the rotational malformation due to the influence of posterior femoral condylar dysplasia; the surgical transepicondylar axis (SEA) serves as a more appropriate reference line for evaluating femoral anteversion (S-tAV) [ 9 ]. The morphologies of the posterior femoral condyles rarely influence the measurement of S-tAV, with a value of >20.4° indicating pathology.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the ideal segment for performing femoral osteotomy, many authors have recently evaluated the position of the increased femoral anteversion. It has been found that the increased of the femoral shaft and distal femoral torsion is most noticeable in patients with patellar dislocation [1,[7][8][9]. However, many authors previously found that patients with patellar dislocation often developed bone malformations of the femoral condyle [10][11][12][13], and therefore, bone malformations of the distal femur is likely to result in internal torsion of the distal femur.…”
Section: Introductionmentioning
confidence: 99%
“…However, no consensus has been reached on the threshold of correction of femoral anteversion. Several scholars have reported that torsional deformity of femoral shaft plays a major role in the femoral torsion, while torsion of distal femur plays a minor role [1,7,9]. It has not yet been reported whether local torsion of distal femur is an independent risk factor for patellar dislocation in patients with patellar dislocation but free of significant femoral anteversion.…”
Section: Introductionmentioning
confidence: 99%